Edukasi dan Pelatihan Pengolahan Limbah Rumah Tangga Menjadi Kompos dan Air Lindi di Desa Purwosari Sayung Demak - Ilham Bayu Pamuji; Ahmad Saeful Fatoni; Muhammad Shodiq; Muhammad Asyrofi; Putri Ayu Anggaraeni; Sufindra Mukti Wibowo; Arum Ambarsari (BADAN PENERBIT STIEPARI PRESS, 2025)
Household waste management remains a key environmental issue in Indonesia, including in Purwosari Village, Sayung District, Demak Regency. The increasing waste volume without proper handling may cause pollution and health problems. Through the Student Organization Capacity Strengthening Program (PPK Ormawa) of the Muhammadiyah Student Association (IMM) Asy-Syifa, Universitas Muhammadiyah Semarang, an education and training program on processing household waste into compost and leachate was carried out to empower the community in sustainable waste management. The activity applied an educational and participatory approach involving housewives through counseling, practice, and interactive discussions. Its effectiveness was evaluated using pre-test and post-test assessments. Results showed a significant improvement in knowledge and skills, with the average score rising from 80 to 92.88, indicating positive behavioral change toward environmental awareness. Participants also began applying the principles of Reduce, Reuse, and Recycle (3R) in daily life. This program contributed to enhancing environmental awareness and reducing household waste volume.